The Strategic Role of School Principals in Preventing and Handling Bullying in Schools - Imam Ghazali; I Istanto; Bambang Sumardjoko; Farouq Muhammad Najib (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Objective: This study aims to analyze the strategic role of school principals in preventing and addressing bullying behavior in schools. This research focuses on principals' understanding of the factors causing bullying and the strategies they implement to create a safe and conducive school environment. Methodology: This study employed a descriptive qualitative approach with purposive sampling. Participants consisted of three principals: two elementary school principals and one high school principal, from schools that had experienced bullying. Data collection methods included interviews, observation, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing using triangulation techniques. Results: The research results show that school principals have a good understanding of the factors causing bullying, including those originating from the family environment, peers, and school culture. Principals implement various prevention and response strategies, such as developing anti-bullying policies, developing student character, and collaborating with teachers and parents. Principals also play an active role in handling bullying cases through persuasive approaches and the application of educational sanctions. Application/Originality/ Value: This study emphasizes the importance of principal leadership in creating a safe, child-friendly school environment that is oriented towards protecting students' rights.